(untitled) (Research, Society and Development, 2021)
In Western education, human formation is related to the humanization of man, as he is a being who is not born ready, but needs to be educated/humanized. Omnilateral training proposes a teaching for a generic man, for this, there is a union between work, science and culture. Throughout history, both professional and technological education (PTE) and physical education have undergone changes for social and political reasons. The general objective of this study was to verify the perception of federal professional and technical education students about the role of physical education in their comprehensive and humanized training. The results presented by the research showed that teachers work with a physical education that goes beyond sport for sport, providing students with an experience of a more critical practice, which aims to really contribute to the formation of citizens. The various ways of working the contents together with practical experience will somehow reflect on how students perceive a particular curricular component. And the students realize that there is no comprehensive training without the presence of physical education, as it is an area that deals with the human being as a whole, from its anatomical structure to the development of social connections. The limits present in the study are recognized due to the pandemic period, with no closer contact with the students. It is hoped that this research can contribute to new studies in the field of physical education, which stimulates a look and curiosity in this area of knowledge, which is so rich and wide. This work becomes another piece in the puzzle of scientific knowledge about the relationship between physical education and omnilateral training.